2002
DOI: 10.1053/jhep.2002.35071
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized placebo-controlled study of long-acting octreotide for the treatment of advanced hepatocellular carcinoma

Abstract: Although various types of treatment of hepatocellular carcinoma (HCC) have been tried, the prognosis remains dismal, especially in patients with advanced stage of the disease. Somatostatin analogues exert antitumor effects. HCC have been shown to exhibit somatostatin receptors. The present randomized placebo-controlled study aimed at examining the efficacy of long-acting octreotide (Sandostatin LAR) for the treatment of advanced HCC. Seventy patients were randomized to receive a 2-week course of 250 g short-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
1
13

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 25 publications
1
127
1
13
Order By: Relevance
“…It is impossible to tell from this trial whether this effect on survival was real, and if so, whether it was due to anticancer effects or other effects such as reduction in portal pressure. Subsequent studies with long-acting octreotide analogues have shown less benefit (Raderer et al, 2000;Samonakis et al, 2002) or no benefit (Yuen et al, 2002). In a recent study, patients selected for treatment on the basis of scan positivity were treated with octreotide and, when compared with a control population in a nonrandomised manner, had better outcomes in terms of survival and quality of life (Dimitroulopoulos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is impossible to tell from this trial whether this effect on survival was real, and if so, whether it was due to anticancer effects or other effects such as reduction in portal pressure. Subsequent studies with long-acting octreotide analogues have shown less benefit (Raderer et al, 2000;Samonakis et al, 2002) or no benefit (Yuen et al, 2002). In a recent study, patients selected for treatment on the basis of scan positivity were treated with octreotide and, when compared with a control population in a nonrandomised manner, had better outcomes in terms of survival and quality of life (Dimitroulopoulos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, a treatment that benefits only a subset of patients may still be clinically worthwhile. The very different outcomes in the randomised trials by Kouroumalis and Yuen probably reflect differences in patient selection (Kouroumalis et al, 1998;Yuen et al, 2002). The Yuen study had subjects with more advanced disease, a higher proportion with viral hepatitis, and a median survival of only 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no single agent or combination of agents given systemically leads to reproducible response rates that show beneficial effect of systemic chemotherapy on survival rates [78] . Tamoxifen, octreotide, interferon, and interleukin-2 have not been shown to be effective in treating HCC in randomized controlled clinical trials [79,80] . The increasing knowledge in the molecular structure of HCC as well as the introduction of molecular targeted therapies in oncology have created an encouraging trend in the management of this disease [81] .…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Systemic chemotherapy with different agents is marginally effective against HCC but severely toxic and unassociated with increased survival Bruix and Sherman, 2005). Agents such as tamoxifen , antiandrogens (Grimaldi et al, 1998) and octreotide (Yuen et al, 2002) are completely ineffective.…”
Section: Current Treatmentmentioning
confidence: 99%